The Patient Encounter: Asking Difficult Questions - Kristin Hahn-Cover (Association of American Medical Colleges, 2007)
Abstract Medical student and interns often have difficulty providing care for, and communicating with, patients with mental health concerns. To address this we created this 1-hour interactive session. The PowerPoint presentation, handouts, and scripts for two role-play scenarios are provided. The lecture presents the components, and stresses the importance, of the doctor-patient relationship and focuses on areas that doctors and patients often find difficult to discuss, including: (1) screening for and discussing sexual orientation, (2) intimate partner violence, (3) mood, (4) memory, (5) substance use/abuse, and 6) financial barriers. An additional focus of this presentation is of the particular difficulties international medical graduates may face in both establishing relationships with their patients, and asking difficult questions. By demonstrating the importance of communication with our patients, and providing handouts on language and tools to use in discussing sensitive topics, we intend to improve the comfort and the performance of participants, and thereby to improve the patient care they provide.